The Relationship Between Eating Patterns and the Occurrence of Metabolic Syndrome in the Elderly at the Haijah Hasmah Noor Foundation Nursing Home, North Jakarta - Vionita Indah Amalia; Linda Weni (Eduvest - Journal of Universal Studies, 2026)
Metabolic syndrome is a critical health concern among the elderly, encompassing central obesity, hypertension, hyperglycemia, and dyslipidemia, all of which are increasingly prevalent in nursing home settings. This study aimed to examine the relationship between eating patterns and the occurrence of metabolic syndrome among elderly residents at the Hajjah Hasmah Noor Foundation Nursing Home, North Jakarta, as well as to review these findings from an Islamic health perspective. A quantitative cross-sectional design was employed involving 35 elderly respondents. Data on dietary intake were collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and 24-Hour Food Recall, while metabolic syndrome was assessed through standardized measurements of waist circumference, blood pressure, fasting blood glucose, and lipid profile. Statistical analysis was conducted using the Chi-Square test with a 95% confidence level. The results revealed that 54.3% of respondents were diagnosed with metabolic syndrome. Dietary assessment showed that 60% of respondents had excessive energy intake based on Nutritional Adequacy Rate (AKG) standards. A statistically significant relationship was found between eating patterns and metabolic syndrome (p = 0.013; OR = 6.25), central obesity (p = 0.017; OR = 5.76), and hypertension (p = 0.02; OR = 5.667). However, no significant relationship was established between eating patterns and hyperglycemia (p = 0.139) or dyslipidemia (p = 0.782). From an Islamic perspective, these findings align with the principles of moderation (wasatiyyah), avoidance of excess (isrāf), and the consumption of halal and thayyib foods, reinforcing the spiritual foundation of preventive health in the elderly.